تقييم القدرات المعرفية لمريض باركنسون - طيار، شهيناز (المركز الجامعي بلحاج بوشعيب عين تموشنت, 2024)
تناولت الدراسة الحالية موضوع الفحص السريع للوظائف المعرفية لدى مريض باركنسون حيث استخدمنا لتحقيق ذلك المنهج الوصفي الذي يعتبر المنهج الأنسب لجمع البيانات المرتبطة بمشكلة وفروض البحث. قمنا بتطبيق الأداة المعدلة (MMP) من نسختها الإيطالية إلى النسخة الجزائرية على حالة عياديه مصابة بمرض باركنسون منذ 4 سنوات لفحص قدراتها المعرفية الخاصة بـ: التوجه المكاني والزماني، الذاكرة البصرية الفورية، الحساب الذهني، السيولة اللفظية، الاسترجاع البصري، الليونة الذهنية والتفكير المجرد. اتضح بعد الفحص المعرفي السريع للحالة (د، ر) من وجود اضطرابات معرفية حادة، حيث تحصلت على قيمة 17 من 32 نقطة. بالتالي فقد سمح الفحص المعرفي السريع باركنسون في نسخته المعدلة من تسليط الضوء على الوظائف المضطربة بشكل واسع وكذلك الوظائف التي احتفظت بها الحالة. The current study addressed the topic of rapid examination of cognitive functions in a Parkinson's patient. To achieve this, we used the descriptive approach, which is considered the most appropriate method for collecting data related to the research problem and hypotheses. We applied the modified tool (MMP) from its Italian version to the Algerian version on a clinical case suffering from Parkinson's disease 4 years ago, to examine her cognitive abilities represented in: spatial and temporal orientation, immediate visual memory, mental arithmetic, verbal fluidity, visual retrieval, mental flexibility and abstract thinking. After a quick cognitive examination of case (D, R), it became clear that there were severe cognitive disorders, as it obtained a value of 17/32 points. Therefore, the Rapid Parkinson's Cognitive Screening in its modified version has allowed to highlight the functions that are widely disturbed as well as the functions that have been preserved by the patient.
Keywords: القدرات المعرفية -- الأمراض العصبية -- الاضطرابات المعرفية